2016
DOI: 10.1159/000454779
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Automated Electronic Alerts in Studying Short-Term Outcomes Associated with Community-Acquired Acute Kidney Injury

Abstract: Background/Aims: The use of electronic alerts (e-alerts) may increase the detection rate of acute kidney injury (AKI) since they are sensitive to small changes in serum creatinine. Our aim was to follow-up a cohort of patients presenting to hospital from the community with AKI (community-acquired AKI [c-AKI]), detected through the use of e-alerts, and describe their short-term outcomes regardless of whether they were subsequently admitted to hospital. Methods: Blood samples for all hospital attenders from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This study has demonstrated that the combination of sCA-I and CA-AKI is present in 3.4% of non-elective hospital attendances and is associated with worse outcomes (30-day all-cause mortality, LOS and admission to ICU) than either CA-AKI or sCA-I on their own. The incidence of CA-AKI in this study (5.7%) and the 30-day mortality rate (21.9%) for the whole group is similar to other published studies [5,19]. In this study population the majority (58.8%) of CA-AKI cases were treated with antibiotics for suspected infection.…”
Section: Discussionsupporting
confidence: 89%
“…This study has demonstrated that the combination of sCA-I and CA-AKI is present in 3.4% of non-elective hospital attendances and is associated with worse outcomes (30-day all-cause mortality, LOS and admission to ICU) than either CA-AKI or sCA-I on their own. The incidence of CA-AKI in this study (5.7%) and the 30-day mortality rate (21.9%) for the whole group is similar to other published studies [5,19]. In this study population the majority (58.8%) of CA-AKI cases were treated with antibiotics for suspected infection.…”
Section: Discussionsupporting
confidence: 89%
“…an increase in serum creatinine by at least 0.3 mg/dl within 48 hrs (if baseline serum creatinine < 1.2 mg/dL) or increase in serum creatinine to at least 1.5 times baseline within the prior 7 days ( Table S1 ). AKI was initially defined as CA-AKI if the increase in serum creatinine was observed during the first 48 hrs of hospitalization 3,15. It was deemed that this approach may not detect AKI originating in a community setting, with patients having a high serum level of creatinine at the time of hospital admission.…”
Section: Methodsmentioning
confidence: 99%
“…CA-AKI account for 54.5% to 79.4% of AKI cases 1417. Detection and prevention of CA-AKI are important because the mortality rates associated with CA-AKI measure 25% at 30 days and 45% at 3 years 3,4. Prevention mainly focusses on improving the prescription of drugs and strengthening their monitoring12 as 59.9% to 72.0% of CA-AKI are induced by drugs 16,18…”
Section: Introductionmentioning
confidence: 99%
“…In the hospital setting, e-alerts have been associated with a lower risk of overlooked HA-AKI, severe HA-AKI, improved odds of nephrologist referral, and improved HA-AKI recovery [27]. Similarly, a 3-month descriptive observational study demonstrated the ability to use CA-AKI alerts at the hospital, whether or not patients were actually admitted to the hospital [28]. Similar alerts could be implemented at the primary care level, before the patient requires observation at the hospital, to encourage physicians to provide appropriate education to patients with CA-AKI, to refer patients to nephrologists and/or to discuss the implementation of a cardiorenal protective diet [29, 30].…”
Section: Discussionmentioning
confidence: 99%